Analisis Segmentasi, Penentuan Target, dan Posisi Pasar Gula Kelapa Kristal Beriodium di Jawa Tengah dan Jawa Barat (Studi Kasus Gendis) - Wafiq Priyaghinanto Habibie; Riana Listanti; Dian Novitasari (AGROINTEK, 2022)
Some of the objectives of this study were: 1) To analyze the segmentation of iodized crystal coconut palm sugar. 2) To recognize the targeting of iodized crystal coconut pal sugar. 3) To Identify the positioning of Gendis iodized crystal coconut palm sugar products. Data collection was carried out online and offline in Purwokerto, where online questionnaires were distributed in several areas in Central Java and West Java. for four months, namely the period December 2020 - March 2021. The population in this study were consumers of iodized crystal coconut palm sugar and its potential consumers. The sampling method in this study used a non-probability sampling method with purposive sampling and snowball sampling techniques. Based on characteristics of the respondents, there are 3 market segments of iodized crystal coconut palm sugar were created. The target market chosen is cluster 2 with the characteristics of respondents aged 41 - 50 years, diploma educational background, housewife profession, and monthly expenses range of Rp.1.500.000 - Rp.3.000.000. Based on the biplot analysis, the results of the perception mapping by respondents that the most attached to the iodized crystal coconut palm sugar were taste, color, and texture.